Exopolysaccharides from bacteria and fungi: current status and perspectives in Africa. Issue 6 (June 2020) - Osemwegie, Osarenkhoe Omorefosa; Adetunji, Charles Oluwaseun; Ayeni, Eugene Ayodele; Adejobi, Oluwaniyi Isaiah; Arise, Rotimi Olusunya; Nwonuma, Charles Obiora; Oghenekaro, Abbot Okotie
Abstract: Bacterial and fungal exopolysaccharides (EPSs) are extracellular metabolites of living organisms (plants, animals, algae, bacteria and fungi) associated with adaptation, survival and functionalities. The EPSs also afford humans multiple value-adding applications across different spheres of endeavors. The variable chemical and biochemical architecture that characterizes an EPS presets its biological functionality and potential biotechnological benefits. Suffices to say that it is amenable to genetic, biotechnological and biochemical maneuverability for desired bioactivity or application during their production and extraction. EPSs have been shown to have, antioxidant, anti-tumor and antiviral activities; enhance soil aridity and nutritional value of food consumed by humans. Their innocuous domestic and commercial versatility and biotechnological relevance is a reliable confirmation of the recent attention accorded EPSs by the global research community. This is especially with respect to their biosynthesis, composition, production, structure, characterization, sources, functional properties and applications. It is also responsible for the development of newer strategies for their extraction. EPSs' relative prospects, perspectives and orientation in the African context are seldom reported in recognized scientific literature data bases. A random preliminary study showed that EPS applications, biotechnological and research orientations are still developing, and influenced by preponderant vegetation, level of industrialization, political will and culture. Africa is endowed with untapped bioresources (biomaterials), bioproducts and bioequivalents that can mediate several global foods, industrial and technological challenges for which EPS may be a potential remedy. Abstract : Africa; Antibacteria; Biotechnology; Exopolysaccharide; Glycosidic bond; Chemistry; Food Science; Agricultural science; Environmental science; Biological sciences.